Factors influencing online purchasing intention among private sector workers in Malaysia / Nini Hartini Asnawi ...[et al.] - Asnawi, Nini Hartini; Ramlee, Nur Atiqah Zakiyyah; Abd Rahim, Lina Nadia; Salleh, Nor Fazalina; Ghazali, Norfazlina; Mohd Yussof, Mohamad Nazim (Faculty of Business and Management UiTM Shah Alam, 2020)
The propose of this research study is to identify for the relationship social media usage and the effectiveness to encourage people to do online purchasing and also their intention to buy. This study focuses on workers from private sector. The literature reviews on the main issues about the power of social media in influencing people with online purchase. Correlation Research is suitable for this research study to find the solution for the problem stated. Therefore, in order to get the significant results and findings, survey research method is applied by distributing a set of questionnaires to the target respondents among private sector workers. There are three research objectives for this research study. The first one is to determine the relationship of ease of use towards intention to buy. Secondly is to examine the influence of usefulness towards intention to buy. Lastly is to analyze the influence of easiness towards intention to buy. 50 set of questionnaires have been distributed to five different departments in the company conducted using descriptive approach and the instrument used is survey questionnaires for data collection purpose. The sampling technique that has been chosen for this research is Simple Random Sampling. Hence, this research study is also explained and reviewed specifically by the researcher based on the data findings at the end of this research. The results of analyses show ease of use and usefulness does influence online purchase intention.